Tool life during machining of square holes - Dragan, Banjac (Journal of Production Engineering, 1984)
Based on more comprehensive research on the process of machining polygonal holes by drilling, the article presents part of the results of testing the tool wear model and tool life in the machining of square holes. For the studied original polygonal tool, the relevant tool wear parameters and the reliable tool life function during machining of mild steel samples are presented.